STATEGI KOMUNIKASI DAKWAH USTADZ FAUZAN YAYAN DALAM MENINGKATKAN SIFAT QANA’AH MASYARAKAT KOTA PALEMBANG - Muhammad Randicha Hamandia (Program Studi Komunikasi dan Penyiaran Islam UIN Raden Fatah Palembang, 2020)
With the nature of qana'ah, peace of life can be achieved. In order to improve the qana'ah nature of the people of Palembang city, the implementation of the communication strategy of Ustadz Fauzan Yayan is very important for Ustadz Fauzan Yayan. The purpose of this study was to determine how the communication strategy of Ustadz Fauzan Yayan's da'wah communication in improving the qana'ah character of the people of Palembang city. This study used qualitative research methods. The data collection techniques used observation, interviews and documentation. The subjects in this study were 10 people in Palembang city. The results of this study indicate that (a) the da'wah communication strategy has been implemented by Ustadz Fauzan Yayan in order to improve the qana'ah nature of the people of Palembang, namely the al-hikmah method, the al-mau'idzah hasanah method, and the al-mujadalah method and (b ) the qana'ah nature of the people of Palembang city after the implementation of the da'wah communicationstrategy has increased both in aspects (1) willingly accepting what is there, (2) asking Allah SWT for appropriate additions and keep trying. (3) patiently accepting God's provisions, (4) putting their trust in Allah Almighty, and (5) not being attracted by the deceit of the world.